Water Movement in the Soil with Different Pore Characteristics and Its Effect to Crop Water Availability - ENNI D. WAHJUNIE; O. HARIDJAJA; SOEDODO H.; . SUDARSONO (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2008)
The understanding of water movement in the soils plays an important role for crop water availability. Up to now, crop water availability in dryland still has a problem. Rainfall is the main source of crop water availability in dryland, but it is unpredictable to cover crop water requirements. To optimize the crop water availability in dryland, the study of the relationship between water movement, rainfall, and soil pores characteristics in the soils is required. This research was aimed to investigate the water movement in the soils with different soil pores due to the difference of soil management. The study was conducted at three blocks of lands with the soil type of Inceptisols, located at Bojong Village, Kemang Sub DIstrict, Bogor District in 2006. The soils investigated were abandoned large frog (Ipomoea reptans), paddy, and peanuts that reflected soil management. The data measurements were focused on water content, rainfall, climatedata, water flux, transient water movement, and water distribution. The results showed that the water fluxes and the transient water movements were significantly affected by the amount of rainfall. The water fluxes in the abandoned peanuts were significantly higher than those at the other lands, while the transient water movements at abandoned paddy field were significantly higher than those at the land with large frog and peanuts. The soil water content during the growing season at the abandoned paddy field was significantly higher compared to the other lands. The amount of rainfall which are held in the soils during the growing season at the abandoned peanuts was significantly high. The result of this research can be use to estimate crop water requirement for irrigation.